Goldilocks and the three bears - Punter, Russell; Alvarez, Lorena (Usborne Publishing Ltd. London, England, 2015)
Someone's been eating my porridge! growled Daddy Bear. A beautifully illustrated retelling of this favourite traditional story. Join the three bears as they try to find out just who has been in their house!